2021
DOI: 10.1159/000516745
|View full text |Cite
|
Sign up to set email alerts
|

Post-Progression Survival Influences Overall Survival among Patients with Advanced Non-Small Cell Lung Cancer Undergoing First-Line Pembrolizumab Monotherapy

Abstract: <b><i>Background:</i></b> Among patients with non-small cell lung cancer (NSCLC), the impact of first-line treatment on overall survival (OS) may be influenced by subsequent therapies. Thus, using patient-level data, we assessed the relationships of progression-free survival (PFS) and post-progression survival (PPS) with OS among patients with high-programmed death-ligand 1 (PD-L1) expression undergoing first-line pembrolizumab monotherapy for NSCLC. <b><i>Methods:</i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(42 reference statements)
0
5
1
Order By: Relevance
“…11 Several studies found that PPS following first-line chemotherapy for advanced NSCLC at the clinical trial level is strongly correlated with OS; 14,15 similar studies examined the impact of PPS in ED-SCLC and advanced NSCLC based on individual patient-level analysis of the strong correlation between OS and PPS. [16][17][18][19]28,29 In contrast to the previous reports, 26,27 we found that PFS does not necessarily reflect OS in patients with ED-SCLC treated with AteCE, but rather that PPS strongly influences OS. The results show that PFS is shorter than PPS, PPS influences OS intimately, and the relationship is linear.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…11 Several studies found that PPS following first-line chemotherapy for advanced NSCLC at the clinical trial level is strongly correlated with OS; 14,15 similar studies examined the impact of PPS in ED-SCLC and advanced NSCLC based on individual patient-level analysis of the strong correlation between OS and PPS. [16][17][18][19]28,29 In contrast to the previous reports, 26,27 we found that PFS does not necessarily reflect OS in patients with ED-SCLC treated with AteCE, but rather that PPS strongly influences OS. The results show that PFS is shorter than PPS, PPS influences OS intimately, and the relationship is linear.…”
Section: Discussioncontrasting
confidence: 99%
“…Before receiving therapy, all patients underwent systematic evaluation and standardized staging procedures. The clinical stage was assigned based on the results of physical examination, chest radiography, thoracic and abdominal computed tomography (CT), brain magnetic resonance imaging or CT, and bone scintigraphy or 18 Ffluorodeoxyglucose positron emission tomography to assess the tumor-node-metastasis (TNM) stage. Clinical stage III/IV SCLC was evaluated per the Union for International Cancer Control TNM classification, eighth edition.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival was analyzed using the Kaplan–Meier method and Cox regression analysis. The correlations among OS, PFS, and PPS were assessed by Spearman’s rank correlation coefficients and linear regression analyses without censored cases as described previously [ 26 ]. The correlations for survival were also tested using data from 450 metastatic urothelial carcinoma cases treated with pembrolizumab in another study cohort [ 27 ].…”
Section: Methodsmentioning
confidence: 99%